Nanomaterial-Based Drug Delivery Systems Therapeutic and Theranostic Applications - Pardeshi, Chandrakantsing V. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Effective drug delivery systems are essential in maximizing the therapeutic effects of the drugs in question. This book thoroughly analyses recent technological advances in new, nanomaterial-based drug delivery systems for the diagnosis and treatment of various diseases. These systems also have diverse applications in pharmaceutical, biomedical, biomaterial, and biotechnological fields. This book explains the different types of nanocarriers currently in development and covers both therapeutic and theranostic applications of drug-loaded nanocarriers and nanomedicine. Clinical research professionals, industrial pharmaceutical scientists, and veteran drug delivery developers benefit from the unique structure of this book, making it essential for the drug delivery researcher. Students, research scholars, and industrial professionals alike benefit from the current technological advancements, regulatory aspects, and the history of discovery and development in the field of nanomedicine presented in this book.
Section-I: Introduction to nanomaterials for drug delivery -- Introduction to Nanomaterials for drug delivery -- Section-II: Nanomaterials-based drug delivery systems for Therapeutic applications -- Polymer-based nanomaterials -- Lipid-based nanomaterials -- Vesicular nanomaterials -- Hybrid nanomaterials -- Section-III: Nanomaterials-based drug delivery systems for Theranostic applications -- Magnetic nanoparticles -- Quantum dots -- Upconversion nanoparticles -- Gold nanoparticles -- Carbon-based nanoparticles -- Graphene-based nanoparticles -- Section-IV: Nanomaterials toxicity & clinical translation -- Nanotoxicology: an overview -- Patenting nanomaterials: Regulatory aspects -- Clinical perspectives: Translating nanomaterials from laboratory to clinic.
Keywords: Pharmaceutical chemistry; Nanomedicine; Toxicology; Pharmacology; Pharmaceutics; Nanomedicine and Nanotoxicology; Toxicology; Pharmacology; Medical Toxicology